2018
DOI: 10.1016/j.sab.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pressure in a plasma produced by laser ablation of steel

Abstract: We investigated the time evolution of pressure in the plume generated by laser ablation with ultraviolet nanosecond laser pulses in a near-atmospheric argon atmosphere. These conditions were previously identified to produce a plasma of properties that facilitate accurate spectroscopic diagnostics. Using steel as sample material, the present investigations benefit from the large number of reliable spectroscopic data available for iron. Recording time-resolved emission spectra with an echelle spectrometer, we we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Other important computational and experimental studies on laser-induced shock waves were performed by Harilal and coworkers [12][13][14], in the framework of extensive and articulated research devoted to the study of the expansion of the laser plume in different ambient gases and experimental configurations [15][16][17][18][19][20]. In a recent paper, Hermann et al [21] studied the Figure 3. Expansion of the spherical shock wave produced by a Nd:YAG laser in gas (black points: Air at pressure of 760 torr; red points: Nitrogen at 760 torr; and blue points: He at 2100 torr).…”
Section: Introductionmentioning
confidence: 99%
“…Other important computational and experimental studies on laser-induced shock waves were performed by Harilal and coworkers [12][13][14], in the framework of extensive and articulated research devoted to the study of the expansion of the laser plume in different ambient gases and experimental configurations [15][16][17][18][19][20]. In a recent paper, Hermann et al [21] studied the Figure 3. Expansion of the spherical shock wave produced by a Nd:YAG laser in gas (black points: Air at pressure of 760 torr; red points: Nitrogen at 760 torr; and blue points: He at 2100 torr).…”
Section: Introductionmentioning
confidence: 99%
“…According to their large initial density, the processes of relaxation are faster whereas the diffusion processes are slower [7,8]. Due to the high initial pressure, the ablated material plume expands rapidly until it reaches a pressure equilibrium with the surrounding gas atmosphere [9,10]. It was shown that for laser irradiation with ultraviolet nanosecond laser pulses, the plasma appears almost uniform if ablation occurs under an inert gas atmosphere [11].…”
Section: Introductionmentioning
confidence: 99%
“…The temperoral evolution was approximated by functions f (t) = At B represented by the continuous lines. This approximation was shown to describe closely the variations n e (t) and T (t) in plasmas produced by laser ablation of different materials under indentical irradiation conditions [32,40,24]. (0,0) Figure 9: Molecular bands and atomic transitions emitted from major and most abundant minor elements.…”
Section: Selection Of Analytical Transitionsmentioning
confidence: 81%
“…The atmospheric pressure is here an arbitrary choice that corresponds to a time between the early and late measurements [40]. According to the strong dependence of the chemical equilibrium on temperature and the weaker dependence on pressure, the temperature-dependence of plasma species shown in Fig.…”
Section: Calculation Of Plasma Chemical Compositionmentioning
confidence: 99%